Immediate Effect of Physiotherapist-demonstrated Action Observation with Execution for Improving Upper Extremity Motor Function in Stroke: a Pre-post Pilot Study - Shrestha, Shaj; Shrestha, Nistha; Dhalachhe Shrestha, Abhishek; Adhikari, Shambhu Prasad (Journal of Nepal Health Research Council, 2024)
Background: Video-demonstrated action-observation-execution is an effective intervention for motor re-learning in stroke rehabilitation. But customization of video for each task repeatedly questions its feasibility within limited resources, particularly for daily routine practice and in community settings. Physiotherapist-demonstrated action-observation-execution is a practical intervention based on the principle of observation and consecutive repetitions of observed real, live movements. The main objective of this study was to investigate the immediate effect of Physiotherapist-demonstrated action-observation-execution in upper extremity motor training in stroke. Methods: Individuals with stroke were screened and 5 eligible participants were recruited. The research was a pre-post. A single session of Physiotherapist-demonstrated action-observation-execution was administered. A functional “Drinking” task was subdivided into simpler acts and trained. Pre and post intervention assessment of movement time using five hand-and-arm items of Nepali Wolf Motor Function Test were carried out. Global recovery was assessed in the form of Visual Analogue Scale. Results: Paired t-test provided statistically significant difference in total movement time (mean difference=5.04 seconds, standard deviation=1.92, p=0.004) with larger effect size (0.95) indicating impressive improvement in movement time with the training. Substantial difference in global recovery score was noted (mean difference=17.40, standard deviation=3.65, p<0.0001, effect size=1.00) signifying the increased confidence and improved performance of upper extremity post treatment. Conclusions: The findings indicated that Physiotherapist-demonstrated action-observation-execution could be a feasible intervention to train motor functions in participants with stroke. Large-scale studies are recommended to establish the effectiveness of the intervention. Keywords: Action-observation; action-execution; hand function; mirror neuron; stroke.